2016
DOI: 10.1002/2015jd024601
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aerosol optical property and radiative effect for the layer decoupling cases over the northern South China Sea during the 7‐SEAS/Dongsha Experiment

Abstract: The aerosol radiative effect can be modulated by the vertical distribution and optical properties of aerosols, particularly when aerosol layers are decoupled. Direct aerosol radiative effects over the northern South China Sea (SCS) were assessed by incorporating an observed data set of aerosol optical properties obtained from the Seven South East Asian Studies (7‐SEAS)/Dongsha Experiment into a radiative transfer model. Aerosol optical properties for a two‐layer structure of aerosol transport were estimated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Such evaluation, however, can readily be conducted using the unique NASA Micro-Pulse Lidar Network (MPLNET; Welton et al, 2002;Campbell et al, 2002;Lolli et al, 2013Lolli et al, , 2014, established in 1999 to continuously monitor cloud and aerosol physical properties (Wang et al, 2012;Pani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such evaluation, however, can readily be conducted using the unique NASA Micro-Pulse Lidar Network (MPLNET; Welton et al, 2002;Campbell et al, 2002;Lolli et al, 2013Lolli et al, , 2014, established in 1999 to continuously monitor cloud and aerosol physical properties (Wang et al, 2012;Pani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Extending from the optical closure modeling (Bell et al, 2013;Pani et al, 2016a) for regional biomass-burning aerosols, Pani et al (2016b) reported, for the first time, a detailed estimation of direct aerosol radiative effect (DARE) near source regions over northern SAP by using in-situ datasets (i.e., ground-based measurement of aerosol physical, chemical, and optical properties) and a radiative transfer model during the spring of 2013 BASELInE campaign. Their results provided strong evidence that biomass-burning aerosols (mainly water soluble and black carbon) enhance the surface cooling (as high as -33.5 W m -2 in 24-hour mean) as well as atmospheric warming (as high as +24.7 W m -2 ), which could significantly influence the diurnally-averaged radiative energetics.…”
Section: Remote Sensing Of Air Quality and Impact On Radiative Energementioning
confidence: 99%
“…Lulin), due to long-range transport from the Indochina region, has been explained and verified by longterm observations (Chuang et al, 2014) and also by modelsimulated results (Chuang et al, 2016b). Pani et al (2016a) recently investigated the radiative impact of upper-layer BB aerosols from the Indochina region over northern South China Sea. Moreover, Pani et al (2016b) reported a detailed estimation of direct aerosol radiative effect for near source BB aerosols over northern Indochina during the spring of 2013.…”
Section: Introductionmentioning
confidence: 99%